VALUES WHICH ARE REPRESENTED BY THE PATTERNS ON PRA-GUAM SILVER BEADS OF KHMER PEOPLE IN KHAWAO SINARIN VILLAGE SURIN PROVINCE, THAILAND - Klangrit, Suriya (PEOPLE: International Journal of Social Sciences, 2017)
This aims of this study are 1) to study the physical patterns on Pra-guam Silver beads 2) To study the basic beliefs represented by the patterns on Pra-guam Silver beads 3) to Study the doctrines which are represented by the patterns on Pra-guam Silver beads 4) To Study the Values which are represented by the patterns on Pra-guam Silver beads. The qualitative research methodology was used in this study by using in-depth-interviews, Participation and Observation. The key participants of the study were Monks, Experts, Academics and Artisans in Kha-Wao Sinarin Village Surin Province, Thailand. The results were that the patterns consist of ancient patterns transferred down from ancestor. the patterns represented were 1) the lotus flower 2) Ma-Yom seed 3) Phigool flower 4) Hae and 5) Jarl 1) the Lotus flower represents the base of belief in Holy Symbolism 2) Ma-Yom Seed stands for the base belief in Popularity 3) Phigool flower is representive of the Symbolism of Ritualism 4) Hae represents the base belief in Ghost and the Devil 5) Jarl reflects the base of belief in the Power of black Magic. The doctrines which are represented on the patterns of Pra-guam Silver beads were 1) the Lotus flower is a Cultural Symbol to represent respectfulness and humility.2) the Ma-Yom seed is a Cultural Symbol that represents thinking carefully and With Circumspection 3) Phigool flower stands for the equality of humanity and justice. 4) Hae is a Cultural Symbol to reflect the belief in thinking carefullyand solving problems in an appropriate manner 5) Jarl is a Cultural symbol that represents the uncertainly of life and trying to do good things. The Values of the patterns on Pra-Guam Silver beads, Cultural Symbol represented the extrinsic values in regard to the spiritual anchor on faith and life safety and Intrinsic Values represented physical beauty on ethnical identity art or design.